Heterochromatin protein 1 beta regulates neural and neural crest development by repressing pluripotency‐associated gene pou5f3.2/oct25 in Xenopus. Issue 8 (26th February 2021) - Tien, Chih‐Liang; Mohammadparast, Saeid; Chang, Chenbei
Abstract: Background: Heterochromatin protein 1 (HP1) is associated with and plays a role in compact chromatin conformation, but the function of HP1 in vertebrate embryogenesis is not understood completely. Results: Here, we explore the activity of HP1 in early neural development in the frog Xenopus laevis . We show that the three isoforms of HP1, HP1α, β, and γ, are expressed in similar patterns in the neural and neural crest derivatives in early embryos. Despite this, knockdown of HP1β and HP1γ, but not HP1α, in presumptive neural tissues leads to head defects. Late pan‐neural markers and neural crest specifier genes are reduced, but early neural and neural plate border genes are less affected in the morphant embryos. Further investigation reveals that neuronal differentiation is impaired and a pluripotency‐associated gene, pou5f3.2/oct25, is expanded in HP1β morphants. Ectopic expression of pou5f3.2/oct25 mimics the effect of HP1β knockdown on marker expression, whereas simultaneous knockdown of HP1β and pou5f3.2/oct25 partially rescues expression of these genes. Conclusion: Taken together, the data suggest that HP1β regulates transition from precursor to more differentiated cell types during neural and neural crest development in Xenopus, and it does so at least partially via repression of the pluripotency‐associated transcription regulator pou5f3.2/oct25. Key Findings: All 3 HP1 isoforms are expressed in neural and neural crest derivatives in Xenopus. Knockdown of HP1b interferes with neuronal differentiation and neural crest development. The pluripotency‐associated factor pou5f3.2/oct25 is expanded in HP1b morphant embryos. Simultaneous knockdown of HP1b and pou5f3.2/oct25 partially rescues neural and neural crest marker expression.